Auditing Cybersecurity Risks in the Digital Age: Evaluating Strategies and Protocols for Effective Risk Assessment and Mitigation in Cybersecurity Audits Within the Life Insurance Industry in India - Shah, Krunal (Digital Repository of Theses - SSBM Geneva, 2025)
This study explores the effectiveness of cyber security risk assessment and mitigation strategies within the Indian life insurance sector, with a focus on auditing practices amid increasing digital threats and evolving regulatory demands. The research aims to evaluate how organizations adopt cybersecurity frameworks, assess emerging risks, and align their controls with compliance and operational resilience. A qualitative-dominant mixed-methods methodology were employed, comprising semi-structured interviews and structured surveys involving 325 professionals across technology, risk, operations, and compliance functions. Thematic analysis, supported by NVivo, conducted using a three phase coding process grounded in Protection Motivation Theory (PMT). Findings reveal that while standard frameworks like NIST and ISO 27001 are commonly used, they are perceived as only moderately effective, particularly in addressing scalability, third-party risks, and real-time threat detection. Participants highlighted critical gaps in audit frequency, policy responsiveness, and ethical oversight. A Cybersecurity Audit Maturity Model (CAMM) was developed to benchmark organizational readiness across five stages, from reactive to proactive. The study concludes that auditing in the digital age requires a shift from compliance-centric models to dynamic, intelligence-driven frameworks. It recommends integrating continuous monitoring, AI-enhanced audit tools, ethical safeguards, and cross-functional collaboration to enhance cyber resilience. The findings contribute to both academic discourse and practical audit reform, with implications for regulators, auditors, and organizational leaders navigating cybersecurity governance.